Polyrethane Foams Combined with Vaseline Prevents 1st Degree Pressure Injuries in Neurosurgical Surgery Patients: Literature Review - Ester Dinar Lumbantoruan; M. Astrid (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: In the world of healthcare, the prevention of pressure injuries in neurosurgical patients in the operating room is an important aspect to prevent serious complications, such as infection and impaired circulation. Grade 1 pressure injuries, although often considered minor, can have a serious impact on patients' recovery and quality of life. Therefore, effective prevention strategies are urgently needed. Objective: This literature review aims to evaluate the use of Polyurethane Foams combined with Vaseline as a method of preventing 1st degree pressure injuries in neurosurgical patients in the operating room. Methods: The method of writing this literature review article uses a narrative review approach. The data used is secondary data obtained from several databases such as Google Schoolar, PubMed, Science Direct, and Research Gate. The literature search in the preparation of the article uses a period of publication years ranging from 2016 to 2024. Results: Preliminary results show that this combination can significantly reduce the risk of 1st degree pressure injuries. Conclusion: Polyurethane Foams and Vaseline were selected based on their specific properties which were considered to support healing and provide protection. The Munro Scale measurement tool was used as a reference for interventions carried out in moderate and high-risk patients.